2005
DOI: 10.1017/s0265021503001418
|View full text |Cite
|
Sign up to set email alerts
|

Desflurane inhibits platelet function in vitro similar to halothane

Abstract: By impairing platelet aggregation while not affecting alpha-degranulation desflurane has a differential effect on various aspects of platelet activation similar to halothane. Our results are compatible with the hypothesis of an impairment of platelet thromboxane receptor signalling by halothane. We suggest a similar mechanism for desflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Among the inhaled anesthetics, halothane has been known to have a property that inhibits platelet aggregation and increases bleeding time. However, desflurane also inhibits platelet function similar to halothane in an in vitro study [11]. Propofol has an effect on inhibiting human platelet aggregation and intracellular calcium increases induced by proinflammatory lipid mediators [12].…”
Section: Discussionmentioning
confidence: 96%
“…Among the inhaled anesthetics, halothane has been known to have a property that inhibits platelet aggregation and increases bleeding time. However, desflurane also inhibits platelet function similar to halothane in an in vitro study [11]. Propofol has an effect on inhibiting human platelet aggregation and intracellular calcium increases induced by proinflammatory lipid mediators [12].…”
Section: Discussionmentioning
confidence: 96%
“…Huang et al [2] suggested that, because sevoflurane inhibited P-selectin expression, it might be beneficial in patients with thrombotic diseases. In considering desflurane, Berlet et al [3] showed no significant effect on the surface expression of P-selectin. Although sevoflurane did not change the expression of Pselectin, it statistically significantly decreased the expression of CD63 in unstimulated platelets.…”
Section: Discussionmentioning
confidence: 98%
“…It is usually considered that at least 80% inhibition of platelet aggregation is necessary to cause a prolongation of bleeding time [13]. Berlet at al [3] established that desflurane has an inhibitory effect on platelet aggregation. There are no data concerning the effects of desflurane on the expression of GPIIb/IIIa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations